2022
DOI: 10.1155/2022/1058667
|View full text |Cite
|
Sign up to set email alerts
|

Schwann Cells in the Tumor Microenvironment: Need More Attention

Abstract: The tumor microenvironment (TME), which is composed of various cell components and signaling molecules, plays an important role in the occurrence and progression of tumors and has become the central issue of current cancer research. In recent years, as a part of the TME, the peripheral nervous system (PNS) has attracted increasing attention. Moreover, emerging evidence shows that Schwann cells (SCs), which are the most important glial cells in the PNS, are not simply spectators in the TME. In this review artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 100 publications
(123 reference statements)
0
23
0
Order By: Relevance
“…PNI is a histological finding, and there are abundant interactions underlying this phenomenon. Recent basic and molecular studies also support the pathogenesis of PNI in a variety of malignancies [ 10 , 24 , 28 ]. Therefore, PNI is an indicator of aggressive behavior in different malignancies based on both clinicopathological observations and molecular findings.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…PNI is a histological finding, and there are abundant interactions underlying this phenomenon. Recent basic and molecular studies also support the pathogenesis of PNI in a variety of malignancies [ 10 , 24 , 28 ]. Therefore, PNI is an indicator of aggressive behavior in different malignancies based on both clinicopathological observations and molecular findings.…”
Section: Discussionmentioning
confidence: 95%
“…PNI has also been widely investigated and recognized as an indicator of aggressive tumor behavior in other malignancies [ 9 , 10 , 11 , 24 ]. For example, Knijn et al reported that the incidence of PNI in patients with colorectal cancer was approximately 18.2% and increased with the severity of T and N status, poor differentiation, and the presence of lymphatic or vascular invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we did not investigate the impact of combined perioperative use of SP600125 and U0126, nor did we evaluate the effect of different dosages or the extended use of either compound on the incidence pf adenomyosis. In light of the role of SCs in the facilitation of EMT [ 30 ], FMT [ 78 ] and fibrogenesis [ 83 ], it is conceivable that continued suppression of SC dedifferentiation is likely to hinder the progression of adenomyosis through impeding EMT, FMT and fibrogenesis. Future studies are needed to clarify these issues.…”
Section: Discussionmentioning
confidence: 99%
“…SCs are the most important type of glial cells in the peripheral nerve system (PNS) and are distributed nearly ubiquitously in the human body [ 27 ]. Their abundance, coupled with their remarkable plasticity that is capable of dedifferentiating and re-differentiating following injury to the nerve, gives them important roles in tissue repair and in promoting cancer progression [ 26 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further research found that autophagic Schwann cells exert a “nerve-repair like effect” to promote perineural invasion in pancreatic cancer ( Zhang et al, 2022a ). These results indicate that autophagy in Schwann cells is an important factor for maintaining the innervated niche and suggests targeting Schwann cells with autophagy inhibitors as a possible tactic for eliminating tumors ( Sun et al, 2022 ).…”
Section: Autophagy In the Innervated Niche Regulates Tumor Progressionmentioning
confidence: 91%